A tool for theory development in action research: a challenge and a resource for nursing research - Mary Casey; David Coghlan; Áine Carroll; Diarmuid Stokes (International Journal of Nursing Studies Advances)
Action research is about action and research: both practice and theory. Theory development takes place throughout action research as the co-researchers strive to create meaning from their experiences of the change while the change is still occurring. Developing theory in action research may manifest in the creation of academic and practical knowledge. Failure to demonstrate the quality of action research reduces both its scientific value and practical application and so theory generation and development during the action research project maybe limited. Ensuring rigor in action research requires that the researcher is clear about the nature of the action or intervention, the ways in which data are collected and analysed and the processes through which the resulting theory is developed. Therefore, the activities and processes involved in using and generating theory in action research must be clearly reported through manifestation of the quality of the research.This paper explores how a Quality Action Research Checklist (QuARC) tool provides a path to how ‘good theory’ may be generated through action research. It provides some background to the elements chosen for the QuARC and discusses key aspects established in the literature on the role of theory in action research. A second aim is to discuss the four areas in the QuARC tool and explore what action research projects should aspire to under these headings, and particularly how theory development may relate to these headings.